Building a vocabulary of praise among mothers towards their children and its relationship with leadership traits - Bany_Yassin, Sujoode Omar Saleh; Ali, Asem Shehadeh Saleh; Abdullah, Mohd Ikhwan (2022)
This study aimed to identify the relationship between building a vocabulary of praise among mothers towards their children and its relationship with leadership traits. The study adapted quantitative research, using a survey methodology, to evaluate the level of a Vocabulary of Praise among mothers towards their children and its relationship with leadership traits. The study sample consisted of (278) respondent from the North Region in Jordanian Society, and electronic questionnaires designed through Google forms were distributed and sent via e-mail to respondents. The results indicated that the respondents' opinions about using praise words were a high level, and the respondents' opinions about leadership traits were a high level. The results showed there is a significant positive relationship between all praise words and leadership traits. The study recommended paying attention to the psychological and emotional support of the child through encouraging help for the child and directing self-reliance. Keywords: Vocabulary of Praise, mothers, children, leadership traits.